2002
DOI: 10.1097/00024382-200212000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Norepinephrine and Dobutamine in Healthy Volunteers

Abstract: The objective of the present study was to evaluate the effects of norepinephrine (n = 9) and dobutamine (n = 7) on carbohydrate and protein metabolism in healthy volunteers in comparison with a control group (n = 9). Norepinephrine (0.1 microg/kg min), dobutamine (5 microg/kg min), or placebo was infused for 240 min. The plasma concentration of glucose, lactate, epinephrine, norepinephrine, insulin, and glucagon were determined. Glucose and urea production and leucine flux were measured using a tracer techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 31 publications
2
25
1
Order By: Relevance
“…This has been demonstrated in both healthy volunteers and in patients in shock of various aetiologies including cardiogenic shock and after cardiac surgery . In agreement with our results, previous studies demonstrated no change in the arterial lactate concentration by administration of intravenous dobutamine or dopamine in adult healthy volunteers and patients . In contrast to our results, an observational study by Li et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This has been demonstrated in both healthy volunteers and in patients in shock of various aetiologies including cardiogenic shock and after cardiac surgery . In agreement with our results, previous studies demonstrated no change in the arterial lactate concentration by administration of intravenous dobutamine or dopamine in adult healthy volunteers and patients . In contrast to our results, an observational study by Li et al.…”
Section: Discussionsupporting
confidence: 92%
“…Dopamine has limited effects on the β 2 ‐adrenoceptors and little effect on the global metabolism. Even though dobutamine does affect the β 2 ‐adrenoceptors mediating vasodilator properties, dobutamine does not seem to have the same effect on the global metabolism as adrenaline . The observed increase in arterial lactate in the milrinone–adrenaline group, in our study, thus may arise from the β 2 ‐adrenergic stimulation of aerobic glycolysis in the skeletal muscle.…”
Section: Discussioncontrasting
confidence: 53%
“…First, the authors confirm the well known effect of epinephrine (in contrast to norepinehrine) of increasing glucose and lactate levels in animal models [10,11,12,13] as well as in humans [14,15,16] in controls. The endotoxin challenge in the present model was associated with decreased mean arterial pressure and systemic blood flow.…”
Section: The Adrenergic Coin: Perfusion and Metabolismsupporting
confidence: 67%
“…Besides inflammatory mediators and counter-regulatory response, the adrenergic agonists administered for cardiovascular therapy (Table 1) may have contributed to glycolysis and increased lactate production. The effect of these agents could not be assessed directly in these severely ill patients but are measurable in healthy subjects (23). The very high insulin concentrations observed are consistent with a marked state of insulin resistance (Fig.…”
Section: Discussionmentioning
confidence: 95%